THE SOURCE OF ENVIRONMENT POLLUTION - WASTE - FESZTEROVA, Melania (Trends in education, 2008)
Each part of human activity is connected with the production of certain amount of waste materials. The waste comes from mining of raw materials and their technological process and consumption too. The waste characteristic and its branching into the Catalogue of Waste according to the waste categories are comparable with The Catalogue of Waste introduced by EC. The waste quantity depends on the industry, the structure of agricultural economical activities and the transport in the region. The trends of their degreasing is connected with the technological standard, but it is also consequent with the realised arrangements, with degreasing of their amount as the tools of environmental policy.In this paper we introduce some topics for the quantity monitoring of waste (solid, liquid, gaseous) in school laboratories in chemistry, ecology and environmental classes.
Keywords: waste; the Catalogue of Waste; monitoring; school laboratory.